Aspek kepastian hukum terkait restitusi dalam perkara perlindungan anak - Erry Fendy Siregar (Jurnal Perspektif Hukum, 2021)
THE ASPECT OF LEGAL CERTAINTY IN RELATION TO RESTITUTION IN THE CASES OF CHILD PROTECTION (A CASE STUDY OF LUBUK PAKAM’S STATE COURT’S VERDICT NUMBER 975/Pid.Sus/2019/PN.Lbp) Article 71 D section (1) of the Act Number 35 Year 2014 on the amendment of the Act Number 23 Year 2002 concerning child protection guarantees that a child who has been a sex crime victim is permitted to lay claim to restitution from the criminal, which is intended to compensate for the loss of wealth, suffering from the crime, and/or medical fees, and/or psychological damage as a form of the criminal’s recompense. Besides, restitution is also intended to soothe the sex crime victim’s distress and enforce justice for them. This study is normative legal research which fostered the descriptive analytic method based on constitutional interpretation, especially that in connection with child protection, and the case interpretation of Lubuk Pakam’s State Court’s verdict number 975/Pid.Sus/2019/Pn.Lbp. This research employed the data collection technique of library review and qualitative data analysis. The verdict number 975/Pid.Sus/2019/PN.Lbp of Lubuk Pakam’s State Court’s judicial panel ordered the convict to pay a restitution of Rp. 1,200,000 (one million two hundred thousand rupiahs) to the victim. The verdict was not apart from the consideration of the fact that it was proven the convict had done the crime referred to by Article 81 section (2) in association with Article 76 D of the Act of Child Protection and the misdeed has caused the victim embarrassment. Moreover, in meting out the sentence, the judicial panel had to take into account the convict’s and social senses of justice. However, in this case, the convict did not pay the specified restitution. From the verdict, it is obvious that there is no guarantee restitution can be paid to the victim soon. What commonly happens is that the convict is not willing or able to pay it. In anticipation of the problem, the prosecutors as the verdict executors can apply Article 38 in association with Article 40 of the Act of Witness and Victim Protection to ensnare the criminal/convict who does not pay restitution to establish the legal certainty of restitution payment to the victim.